Elasticity in Macrophage‐Synthesized Biocrystals. (12th January 2017) - Horstman, Elizabeth M.; Keswani, Rahul K.; Frey, Benjamin A.; Rzeczycki, Phillip M.; LaLone, Vernon; Bertke, Jeffery A.; Kenis, Paul J. A.; Rosania, Gus R.
Abstract: Supramolecular crystalline assembly constitutes a rational approach to bioengineer intracellular structures. Here, biocrystals of clofazimine (CFZ) that form in vivo within macrophages were measured to have marked curvature. Isolated crystals, however, showed reduced curvature suggesting that intracellular forces bend these drug crystals. Consistent with the ability of biocrystals to elastically deform, the inherent crystal structure of the principal molecular component of the biocrystals—the hydrochloride salt of CFZ (CFZ‐HCl)—has a corrugated packing along the (001) face and weak dispersive bonding in multiple directions. These characteristics were previously found to be linked to the elasticity of other organic crystals. Internal stress in bent CFZ‐HCl led to photoelastic effects on the azimuthal orientation of polarized light transmittance. We propose that elastic, intracellular crystals can serve as templates to construct functional microdevices with different applications.